2011
DOI: 10.1074/jbc.m110.177907
|View full text |Cite
|
Sign up to set email alerts
|

A Transmembrane Protein EIG121L Is Required for Epidermal Differentiation during Early Embryonic Development

Abstract: Epidermal differentiation in the ventral ectoderm of Xenopus embryos is regulated by the bone morphogenetic protein (BMP) pathway. However, it remains unclear how the BMP pathway is activated and induces the epidermal fate in the ventral ectoderm. Here, we identify a novel player in the BMP pathway that is required for epidermal differentiation during Xenopus early embryonic development. We show that Xenopus EIG121L (xEIG121L) protein, an evolutionarily conserved transmembrane protein, is expressed in the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…EIG121L plays an important role in epidermal differentiation . EIG121L is a transmembrane protein, and its knockdown causes developmental defects, such as inhibition of epidermal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…EIG121L plays an important role in epidermal differentiation . EIG121L is a transmembrane protein, and its knockdown causes developmental defects, such as inhibition of epidermal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Among individual inflammatory biomarkers' response to fenofibrate, the strongest association was found for CpG associated with the CRP-IL-2sR pattern, located in KIAA1324L (chromosome 7). Human KIAA1324L, or EIG121L, is markedly downregulated by a constitutively active mutant of Ras [35]. At least seven of the top ten genes shown to interact with KIAA1324L were related to inflammation: DLC1, ERBB4, PDCD4, TSPAN3, RPS23, ESR1, TCEAL4 and PDE5A [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our results of whole-mount in situ hybridization definitely indicate that FGF-mediated transcriptional repression of kctd15 contributes to the region-specific expression of kctd15, which might result in the region-specific activation or repression of Wnt signaling that is responsible for proper embryonic development. We recently reported that another Ras-repressed gene, eig121l, is specifically expressed in the ventral ectoderm and acts as a positive regulator of the BMP pathway (Araki et al, 2007;Araki et al, 2011). Thus, FGF/Ras-induced transcriptional repression of signaling molecules may represent a mechanism mediating the crosstalk among multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%